A case report of rare incidence of benign vascular lesion of hand masquerading magnetic resonance imaging findings - Mehta, Pallav S.; Gohil, Aastha R. (International Journal of Research in Orthopaedics, 2025)
Vascular anomalies of hand can present as soft tissue swelling and can be one of differential along with the common ones’ ganglion cyst, giant cell tumor (GCT), and epidermoid cyst. It can be hemangioma or vascular malformation, they differ based on histological, clinical and biological characteristics. A 65-year-old male presented with swelling in right little finger dorsal part since one month. It was insidious in onset and not associated with pain or trauma. Vascular lesions of hand should be kept in mind as one of differential while examining swellings of hand. Initial investigation like ultrasonography (USG), X ray, magnetic resonance imaging (MRI) and fine needle aspiration cytology (FNAC) should always be followed by excisional histopathology for confirmation and labelling the diagnosis.